Microbial and chemical properties of anchovies based fish sauce (BUDU) - Zainudin, Nurnadirah (Universiti Sains Malaysia, 2016)
This study was conducted to assess the microbial load and chemical properties of anchovies based fish sauce made from anchovy, Stolephorus sp with 3:2 fish to salt ratio at 1st day, 1st month, 2nd month, 3rd month, 4lh month and 5th month of fermentation. The samples of the anchovies based fish sauce was taken directly from the budu factory in Tumpat, Kelantan. For microbial load properties analysis, the total plate count was determined using plate count agar (PCA) which was incubated for 48 hours at 37°C. Moreover, chemical properties analysis that are moisture, total ash, crude protein, fat, carbohydrate and pH were determined using standard method. Microbial load for the total plate count (TPC) using pour plate increase significantly from 4.8x103 cfu/mL to l.OxlO4 cfu/mL after 5 months of fermentation. Microbial load using spread plate increase significantly from 6.9xl04 cfu/mL to 1.2x10s cfu/mL. The increase in the TPC at the initial stage of fermentation could be due to bacterial and autolytic spoilage that occurred once the anchovies mixture was prepared. An increase of the microbial load was also due to most of the halophilic bacteria successfully adapted well to high salt environment. Moisture content of samples from 47.37%-59.57% with mean 52.4±4.0. Ash content range from 34.7%-39.4% with mean 36.7±1.9. Result show decreased of fat content throughout fermentation from 4.58% to 1.41% with mean 2.8±1.2. Protein content increased significantly with mean 4.7±0.7 and pH value range from 4.27-5.17. Based on microbiological safety of ready-to-eat foods, spoilage eventually occurred at a level around 109 cfu/mL due to the production of lactic acid. The anchovy based fish sauce from factory in Tumpat, Kelantan showed low level of microbial load thus safe for consumer consumption. The level of moisture and protein in budu samples were higher than value in Malaysian Foods Composition Database (59.6% moisture, 6.4% protein). Protein level also complied with Malaysian Food Act 1983 which stated that budu should contain not less than 5% protein. Ash represents inorganic components and minerals in food and there was high level of minerals in budu products. However, the percentage of fat was lower than the value documented in Malaysian Foods Composition Database (1.4%). The fat content was originated from the addition of salt into fermented fish.